Evaluating the Outcomes of Inclusive Education Policies for Students with Disabilities in Indonesian Schools - Katarzyna Nowak; Piotr Kowalski; Anna Zielinska (International Journal of Educational Evaluation and Policy Analysis, 2024)
This study explores the outcomes of inclusive education policies for students with disabilities in Indonesian public schools. The study analyzed data from schools implementing inclusion programs and conducted interviews with students, teachers, and administrators. Findings indicate improvements in social integration but also highlight ongoing challenges in resource allocation and teacher preparedness. Recommendations for policymakers include strengthening teacher training, increasing resources, and improving monitoring mechanisms to support effective inclusive education practices.